2004
DOI: 10.1097/01.ju.0000118164.39641.98
|View full text |Cite
|
Sign up to set email alerts
|

Normality of Bladder Filling Studied in Symptom-Free Middle-Aged Women

Abstract: To compose a study group of normal volunteers of middle age requires strict inclusion and exclusion. Even then some volunteers must be excluded if pathological examination results are found. Middle-aged women have bladders with large capacity and high compliance, which can be the consequence of retaining urine during daily activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 17 publications
2
36
3
Order By: Relevance
“…Similar data have been perceived in healthy young women and asymptomatic middle-aged women. 3,6 De Wachter and Wyndaele 3 reported that the largest number of voids (46.3%) were graded without desire to void (grade 1) in young female healthy volunteers with an average age of 21 years, while in the present study, the largest number of voids occurred with a perception of desire to void (grade 2). This difference may be due to the age differences in the two studies.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Similar data have been perceived in healthy young women and asymptomatic middle-aged women. 3,6 De Wachter and Wyndaele 3 reported that the largest number of voids (46.3%) were graded without desire to void (grade 1) in young female healthy volunteers with an average age of 21 years, while in the present study, the largest number of voids occurred with a perception of desire to void (grade 2). This difference may be due to the age differences in the two studies.…”
Section: Discussioncontrasting
confidence: 51%
“…3 Similar data have been obtained from asymptomatic middleaged women. 6 Those studies, however, did not focus on OAB syndrome. Our data from bladder diaries which included bladder perception showed void patterns in community-based women and included subjects with urgency and/or urge incontinence.…”
Section: Discussionmentioning
confidence: 98%
“…These characteristics are closely correlated with the frequent void numbers and maximal voiding capacity of less than 350 mL during both the daytime and night-time (daytime frequency 13.1 ± 4.0 vs night-time 3.2 ± 1.8; daytime maximal voided volume 121.3 ± 56.5 mL vs night-time 146.5 ± 76.4 mL, Table 2). Other studies 15,16 showed that the mean voided volume of BPS/IC patients ranges from 75 to 175 mL, which is less than that of asymptomatic people Useful voiding diary in BPS/IC (289 mL). Additionally, the mean number of daytime voids in BPS/IC patients was six times greater compared with asymptomatic individuals (range 17-25 times per day).…”
Section: Discussionmentioning
confidence: 99%
“…All underwent conventional cystometric bladder filling as a test for sensory evaluation of the bladder, because for this technique the normal pattern and normal values of filling sensations have been repeatedly described [9][10][11][12][13]. The use of cystometry as the technique might put some limitations to the study, as inserting a transurethral catheter and filling the bladder artificially might already change the sensory pattern in patients, and it is unknown whether the cystometric filling sensations correlate with the filling sensations during normal daily life.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there was no difference in warning volume in patients that perceived one standardized normal filling sensation. According to cystometric data from normal volunteers, these two patient groups should be labelled as having disturbed filling sensation [9][10][11][12][13]. We think that they represent the most severe form of urgency, as their warning volume is significantly smaller than that of patients with CDV preceded by a normal pattern of filling sensation.…”
Section: Discussionmentioning
confidence: 99%